Crisis Marketing: Features of Application and Ways of Reformation (Economics and region, 2020)
The article defines the problems and opportunities of developing marketing in crisis. The importance of reforming the marketing system before and during the crisis is determined. The peculiarities of the crisis of 2020, its impact on consumer behavior and the development of the economy and marketing in general are analyzed. New motives and features in consumer behavior are highlighted. The factors influencing the development of marketing and advertising are studied. The main directions of development of enterprises, their marketing departments and additional services that can be implemented even by a small company and that will create a circle of loyal customers are highlighted.
Keywords: economic crisis; marketing in crisis; advertising; changes in consumer behavior